2011
DOI: 10.1128/mcb.05734-11
|View full text |Cite
|
Sign up to set email alerts
|

Chlamydia trachomatis Inclusions Induce Asymmetric Cleavage Furrow Formation and Ingression Failure in Host Cells

Abstract: Chlamydia trachomatis infection has been suggested to induce host genome duplication and is linked to increased risks of cervical cancer. We describe here the mechanism by which Chlamydia causes a cleavage furrow defect that consistently results in the formation of multinucleated host cells, a phenomenon linked to tumorigenesis. Host signaling proteins essential for cleavage furrow initiation, ingression, and stabilization are displaced from one of the prospective furrowing cortices after Chlamydia infection. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(31 citation statements)
references
References 54 publications
(74 reference statements)
4
26
0
1
Order By: Relevance
“…Sun et al demonstrated that steric effects of the chlamydial inclusion correlated with multinucleation [8]. Our data show that multinucleation is dependent on centrosome positioning defects, suggesting that the association between the chlamydial inclusion and the centrosomes can cause multinucleation at a low level without centrosome amplification, perhaps by causing steric interference with the centrosomes and the spindle apparatus during cell division.…”
Section: Discussionsupporting
confidence: 54%
“…Sun et al demonstrated that steric effects of the chlamydial inclusion correlated with multinucleation [8]. Our data show that multinucleation is dependent on centrosome positioning defects, suggesting that the association between the chlamydial inclusion and the centrosomes can cause multinucleation at a low level without centrosome amplification, perhaps by causing steric interference with the centrosomes and the spindle apparatus during cell division.…”
Section: Discussionsupporting
confidence: 54%
“…We have previously demonstrated that C. trachomatis inclusions localize very efficiently to the host cell center during telophase using live imaging and IF in synchronized cells [Sun et al, ]. In the current study, we confirmed these observations with live cell DIC imaging in asynchronous cells.…”
Section: Discussionsupporting
confidence: 88%
“…Since Chlamydial protein synthesis played an important role in localizing the inclusion to the cell center to block host cell division [Sun et al, ], we next explored whether blocking host cell division conferred any physiological benefits to C. trachomatis . It has been well documented that the replicative success of C. trachomatis is highly dependent on access to host Golgi lipids [Heuer et al, ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…12 Chlamydia trachomatis was epidemiologically linked to increased risk of developing cervical cancer. 13 It affects genome stability by several mechanisms: multipolar spindle formation, 14,15 spindle assembly checkpoint override, 16 cytokinesis failure, 17,18 and induction of DNA damage coupled to impaired repair mechanisms. 19 The interplay between Lm and the host cell cycle is understudied.…”
Section: Introductionmentioning
confidence: 99%